INFORMATION-MEASURING SYSTEMS FOR MONITORING THE TECHNOLOGICAL PARAMETERS OF ROLLING MILLS - Суботін, Олег; Петрухін, Ярослав; Люта, Анастасія; Новіков, Дмитро (SWorldJournal, 2026)
Rolling mill process control systems require a wide variety of sensors that operate under the extreme conditions of heating plants. This reduces the accuracy and reliability of the results obtained and causes significant material losses, the occurrence of